PENGARUH PENGGUNAAN AIR POLISHER DENGAN BAHAN SODIUM BIKARBONAT TERHADAP GAYA GESEK BRAKET LOGAM DAUR ULANG - , AFINI PUTRI LUTHFIANTY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Air Polisher Devices ( APDs ) is a tool that works by pushing the particles pass through a mixture of water and polish air through the end of the handpiece with a certain pressure pipe . One type of powder used APDs is sodium bicarbonate . The use of APDs results in soft tissue , hard tissue , restorative materials and loss of stain . The purpose of this study was to determine the effect of water use sodium bicarbonate polisher made against frictional forces recycled metal bracket . This study uses 30 metal edgewise premolar bracket with slot size of 0.022 \" are divided into two groups ( group I with recycled combustion , and group II with recycled combustion followed by water polishing ) and 30 straight stainless steel rectangular wire size 0.016 \" x 0.022 \" along the 10 cm . Frictional force was measured using a Universal Testing Machine ( UTM ) and bracket shooting microscopically using a Scanning Electron Microscope ( SEM ) with a magnification of 100x . The data obtained is then performed statistical analysis Test T. The results showed that there were significant differences in the frictional forces (p <0.05) in the group of burning metal bracket recycled water followed by polishing with a metal bracket without burning recycled water followed by polishing. The mean frictional forces group bracket recycling with combustion and water followed by polishing was 1.46 N and the group bracket recycling with combustion without water followed by polishing is 1.63 N. The conclusion of this study is the frictional force of recycled metal bracket with combustion and water polishing followed by smaller when compared to recycled metal bracket without water followed by polishing. Keywords: friction forces, bracket metal recycling, combustion, Air Polisher Devices (APDs)